Maternal vitamin D and markers of glycaemia during pregnancy in the Belfast centre of the Hyperglycaemia and Adverse Pregnancy Outcome study. Issue 7 (20th May 2018) - Casey, C.; McGinty, A.; Holmes, V. A.; Hill, A. J.; Patterson, C. C.; Young, I. S.; McCance, D. R.
Abstract: Aims: To measure total 25‐hydroxyvitamin D levels in women in mid‐pregnancy who participated in the Belfast centre of the Hyperglycaemia and Adverse Pregnancy Outcome (HAPO) observational study, and to investigate the associations between levels of 25‐hydroxyvitamin D and markers of gestational diabetes mellitus and lipid biomarkers. Methods: A total of 1585 pregnant women had serum samples available for measurement. Participants were recruited from the Royal Jubilee Maternity Hospital, Belfast, Northern Ireland, at 24–32 weeks' gestation, as part of the HAPO study. 25‐hydroxyvitamin D concentrations were measured using liquid chromatography tandem mass spectrometry. Glucose, C‐peptide and lipid levels were previously analysed in a central laboratory. Statistical analysis was performed. Results: The median (interquartile range) 25‐hydroxyvitamin D concentration during pregnancy was 38.6 (24.1–60.7) nmol/l, with 65.8% of women being vitamin D‐deficient (≤50 nmol/l). In regression analysis, the association between maternal 25‐hydroxyvitamin D and fasting plasma glucose levels approached significance [regression coefficient –0.017 (95% CI –0.034 to 0.001); P =0.06], and a significant positive association was observed between maternal 25‐hydroxyvitamin D and β‐cell function [1.013 (95% CI 1.001 to 1.024); P =0.031]. Maternal 25‐hydroxyvitamin D level was positively associated with HDL [0.047 (95% CI 0.021 to 0.073) P ≤ 0.001] and total cholesterol [0.085 (95% CI 0.002 to 0.167); P =0.044] in regression analysis. Conclusions: These results indicate a high prevalence of vitamin D deficiency during pregnancy, which requires identification and treatment; however, only weak associations were observed between 25‐hydroxyvitamin D level and markers of glucose and insulin metabolism. This would suggest that these are of doubtful clinical significance. What's new?: This was a large‐scale observational study reporting serum vitamin D concentrations in a pregnant population in Northern Ireland. The study shows a high level of vitamin D deficiency in a white European cohort at 55°N. The study suggests that vitamin D and glucose metabolism in pregnancy are not linked.